Openness and prosperity - Herbert Giersch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
Openness vis-i-vis the world and an improved incentive system at home are the key requirements for a lasting re-acceleration of economic growth in Europe, the U.S. and indeed most parts of the world. More specifically, the policy-oriented message to be propounded in this paper is essentially twofold: (i) Europe could already learn much from the U.S. to improve its incentive system and to make its internal markets more open, (ii) Openness vis-a-vis the world economy is a task to be pushed onto the policy agenda in the U.S. as well as in Europe and Japan. Such international openness involves more competition among governments and central banks, a competition that can support our hopes for limited government and sound money in future decades.
Keywords: 330; Wirtschaftswachstum; Ökonomischer Anreiz; Wirtschaftsliberalismus